2014
DOI: 10.1093/mp/ssu131
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a novel lodging resistance QTL gene involved in strigolactone signaling and its pyramiding with a QTL gene involved in another mechanism

Abstract: Lodging has been a major roadblock to attaining increased crop productivity. In an attempt to understand the mechanism for culm strength in rice, we isolated an effective quantitative trait loci (QTL), STRONG CULM3 (SCM3), the causal gene of which is identical to rice TEOSINTE BRANCHED1 (OsTB1), a gene previously reported to positively control strigolactone (SL) signaling. A near-isogenic line (NIL) carrying SCM3 showed enhanced culm strength and increased spikelet number despite the expected decrease in tille… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 0 publications
0
30
0
Order By: Relevance
“…Based on results presented here, the improved fertility of lateral spikelets in barley lines that carry loss-of-function mutant alleles of HvTB1 may be explained by reduced dormancy of the lateral spikelet primordia and associated with increased expression of meristem identity genes within the lateral spikelets. This hypothesis is supported by results from rice showing that an OsTB1 allele (SCM3) that confers increased TB1 expression is associated with increased dormancy of axillary meristems to form inflorescences with more primary and secondary panicle branches and that transcript levels of MADS box genes were altered by overexpression of OsTB1 (Yano et al, 2015). Interestingly, the maize Tb1 allele has been linked recently to negative transcriptional regulation of MADS box genes in the context of glume development, by suppressing transcription of the Squamosa Promoter Binding protein transcription factor, teosinte glume architecture1 (Studer et al, 2017).…”
Section: Discussionmentioning
confidence: 75%
“…Based on results presented here, the improved fertility of lateral spikelets in barley lines that carry loss-of-function mutant alleles of HvTB1 may be explained by reduced dormancy of the lateral spikelet primordia and associated with increased expression of meristem identity genes within the lateral spikelets. This hypothesis is supported by results from rice showing that an OsTB1 allele (SCM3) that confers increased TB1 expression is associated with increased dormancy of axillary meristems to form inflorescences with more primary and secondary panicle branches and that transcript levels of MADS box genes were altered by overexpression of OsTB1 (Yano et al, 2015). Interestingly, the maize Tb1 allele has been linked recently to negative transcriptional regulation of MADS box genes in the context of glume development, by suppressing transcription of the Squamosa Promoter Binding protein transcription factor, teosinte glume architecture1 (Studer et al, 2017).…”
Section: Discussionmentioning
confidence: 75%
“…Bending strength was negatively correlated with number of ear bearing tillers plant -1 , panicle length and culm strength and positively associated with test weight and basal inter nodal length. Negative association of SCM3 and SCM4 QTLs conferring for bending strength with number of productive tillers per plant was observed by Yano et al, (2014). Lower elongating internodes have negative association with ear bearing tillers per plant.…”
Section: Identification Of Lodging Resistant Lines Using Phenotypic Cmentioning
confidence: 93%
“…Several workers reported QTLS for culm diameter (Ookawa et al, 2010), culm thickness (Mu et al, 2004), culm strength (Zhu et al, 2008;Yamamoto et al, 2013;Yano et al, 2014), basal internodal length (Mu et al, 2004) will be useful in selection of lodging resistant lines in early generations. Hence present study aimed to screen F 3 families for lodging resistance using molecular markers and phenotypic screening.…”
Section: Issn: 2319-7706 Volume 7 Number 01 (2018)mentioning
confidence: 99%
See 1 more Smart Citation
“…Yield per area is determined by four yield components: the number of panicles per area (PN), the number of spikelets per panicle (SN), thousand grain weight (TGW), and the percentage of ripened grain (RP). Recently, several genes and quantitative trait loci (QTLs) that regulate the SN, such as Grain number 1a (Gn1a) (Ashikari et al, 2005), DENSE AND ERECT PANICLE1 (DEP1) (Huang et al, 2009), ERECT PANICLE (EP) (Wang et al, 2009), ABERRANT PANICLE ORGANIZATION 1 (APO1) (Ikeda-Kawakatsu et al, 2009), STRONG CULM2 (SCM2) (Ookawa et al, 2010), TAWAWA1 (TAW1) (Yoshida et al, 2013), SQUAMOSA PROMOTER BINDING (Jiao et al, 2010;Miura et al, 2010), SPIKELET NUMBER (SPIKE) (Fujita et al, 2013), and STRONG CULM3 (SCM3) (Yano et al, 2015), have been identified, and the near-isogenic lines (NILs) for high SN have been developed. However, since the four-yield components are often negatively correlated, the introduction of these genes may not always increase the yield in the field.…”
Section: Open Accessmentioning
confidence: 99%